FUNCTIONAL ANALYSIS OF EARLY BYZANTINE CONTEXTS AT SAGALASSOS - Putzeys, Toon; Poblome, Jeroen; Bes, Philip (Rei Cretariae Romanae Fautorum Acta, 2024)
Using the archaeological record to identify human activities and their social and economic implications is one of the most difficult but at the same time one of the most interesting aspects of archaeology. Reconstructing the fabric of daily life is difficult because it requires a comprehensive study of all available evidence including structures, site formation processes, artifacts, food and plant remains. A full integration of the diverse data of the archaeological record is necessary as assumptions based on one particular material category can be contradicted by the presence of certain other objects.